Impurity behaviour in JET high-current baseline scenario for Deuterium, Tritium and Deuterium-Tritium plasmas - N. Wendler; A. Chomiczewska; W. Gromelski; E. Kowalska-Strzęciwilk; G. Telesca; I. Ivanova–Stanik; L. Garzotti; D. Van Eester; V.K. Zotta; D. Frigione; F. Rimini; G. Pucella (Nuclear Materials and Energy)
To support future ITER operation, experimental campaigns at the Joint European Torus (JET) with an ITER-like wall (tungsten divertor and beryllium main chamber) in pure deuterium (D), tritium (T) and Deuterium-Tritium (D-T) were performed. One of the most important challenges in recent years was the development of two main scenarios that investigated different approaches to achieve the high fusion power as well as good plasma confinement (Garzotti et al., 2023). The first one, so-called baseline scenario is relying on high plasma current (Ip≈3.5 MA), normalized beta βN < 2 and safety factor q95 ≈ 3 (Garzotti et al., 2023). On the other hand, the second one, so-called Hybrid scenario is operating at lower plasma current (flat-top Ip ≤ 2.6 MA) and density with respect to the baseline, higher normalized beta βN > 2 and safety factor q95 ≈ 4.8 (Hobirk et al., 2023).In this paper we focus on the impurity behaviour analysis for the baseline discharges at Ip = 3.5 MA and BT = 3.3 T with D, T and DT plasmas, in which the gas and power waveform were optimized to achieve the best possible performance. In particular, we study the impact of total heating power (Ptot + Palpha), flat-top gas flow and ELM (edge localized modes) frequency on mid-Z (Nickel (Ni), Copper (Cu)) and high-Z (Tungsten (W)) impurities. In addition, we compared the two best performing pulses of the baseline scenario (Ip = 3.5MA, BT = 3.3 T and Pin ≈ 35 MW) in D and DT in order to identify the causes responsible for the increase in radiation during the DT pulse, which led to an early plasma termination. All presented results rely on the data collected by the VUV as well as the bolometry system. Detailed analysis indicates that in the baseline scenario, higher radiation, which is most likely due to the tungsten (W), is observed for T and DT plasmas in comparison to D. Moreover, for the two best performing baseline pulses, tomographic reconstructions show that the radiated power density is mainly emitted from the low field side (LFS) of the plasma and W does not accumulate in the plasma center (Telesca et al., 2024).